2022
DOI: 10.1111/dar.13428
|View full text |Cite
|
Sign up to set email alerts
|

The who and what of women's drinking: Examining risky drinking and associated socio‐demographic factors among women aged 40–65 years in Australia

Abstract: Introduction. Recent trends in Australian national survey data show an increase in alcohol use among middle-aged people, amidst declines in alcohol use among other population groups. There is limited research, however, on middle-aged women's alcohol use. This study aimed to examine patterns in alcohol use among Australian women aged 40-65 and the associated sociodemographic and contextual factors. Methods. Cross-sectional data from six waves of the National Drug Strategy Household Survey (2001)(2002)(2003)(200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…consuming more than five standard drinks per day increases breast cancer risk by as much as 61%) [7]. The current study builds upon recent research by Miller et al [18], which identified just over one in 10 mid–older‐aged women from the Australian general population to be drinking at a risky level according to previous 2009 national guidelines.…”
Section: Discussionmentioning
confidence: 88%
“…consuming more than five standard drinks per day increases breast cancer risk by as much as 61%) [7]. The current study builds upon recent research by Miller et al [18], which identified just over one in 10 mid–older‐aged women from the Australian general population to be drinking at a risky level according to previous 2009 national guidelines.…”
Section: Discussionmentioning
confidence: 88%
“…The importance of the role of alcohol in breast cancer and preventive interventions is increasing with the rise in alcohol consumption among older women, in contrast to declining consumption in other population groups 6 . Why women over 40 are drinking more alcohol is a complex and multifaceted question.…”
mentioning
confidence: 99%
“…Alcohol consumption at any point in life increases the risk of breast cancer, but recent use, in particular, influences breast cancer risk, especially for women over 40 years of age 6 . While alcohol consumption is declining in Australia, long term risky drinking (two or more standard drinks per day) has increased among women aged 40 years or more 7,8 . Increases in alcohol consumption by middle‐aged and older women have also been reported overseas, 9 but alcohol drinking in these age groups is not targeted by large scale breast cancer prevention programs.…”
mentioning
confidence: 99%
“…6 While alcohol consumption is declining in Australia, long term risky drinking (two or more standard drinks per day) has increased among women aged 40 years or more. 7,8 Increases in alcohol consumption by middle-aged and older women have also been reported overseas, 9 but alcohol drinking in these age groups is not targeted by large scale breast cancer prevention programs.Brief alcohol interventions are recommended by the recently updated Australian guidelines for the treatment of alcohol problems. 10 Brief interventions can improve alcohol literacy and reduce consumption when delivered in general practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation